Rare Variants in the Epithelial Cadherin Gene Underlying the Genetic Etiology of Nonsyndromic Cleft Lip with or without Cleft Palate. Issue 11 (3rd August 2015) - Brito, Luciano Abreu; Yamamoto, Guilherme Lopes; Melo, Soraia; Malcher, Carolina; Ferreira, Simone Gomes; Figueiredo, Joana; Alvizi, Lucas; Kobayashi, Gerson Shigeru; Naslavsky, Michel Satya; Alonso, Nivaldo; Felix, Temis Maria; Zatz, Mayana; et al.
<x xml:space="preserve">Abstract</x> Rare, moderately penetrant variants in the epithelial cadherin gene consist in a promising risk factor for nonsyndromic cleft lip/palate. We highlight the importance of such variants in familial cases, and we suggest haploinsufficiency of CDH1 as the probable mechanism. To speculate why some CDH1 pathogenic variants may alternatively result in gastric cancer, we suggest a two‐hit model underlying both phenotypes.